Performance analysis of catch fisheries in Sabang Waters - Salmarika Salmarika; Imam Shadiqin; Muhammad Irham; Imelda Agustina; Rosi Rahayu; Ratna Mutia Aprilla; Alvi Rahmah (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2022)
Sabang waters is one of the centers of capture fisheries production at the tip of the Sumatera Island which has a large potential of fish resources. However, information related to the performance of capture fisheries including fish production, fishing gear, fishing fleet, number of fishermen and fishing areas is still limited. This study aims to analyse and describe information related to capture fisheries performances in the waters of Sabang. Performance data were analysed descriptive quantitatively and obtained by survey method. The results showed that the trend of capture fisheries production tends to increase by 15% annually and catches are dominated by large pelagic fish, namely tuna (Thunnus sp). The type of fishery business is dominated by fishermen who operate vessels measuring 0 - 5 GT (57.9%) with fishing areas between the coast to 2 nautical miles. Fishermen in Sabang Waters are categorized as small businesses. because use small boats and using handlines as fishing gear that aim to meet daily needs, not for business scale.Keywords:Fish productionFishing gearFishing fleetFishing groundCapture fisheries